Faktor-Faktor yang Berhubungan dengan Ketepatan Waktu Vaksinasi Meningitis pada Jamaah Umrah (Studi di Kota Bengkulu) - Ernawati Heriansyah; Ari Udiyono; Martini Martini; Lintang Dian Saraswati (Jurnal Epidemiologi Kesehatan Komunitas, 2020)
Background: Meningococcal meningitis is a disease with high morbidity and mortality which, if left untreated, 100% will end in death. Meningitis vaccination is a way to prevent transmission of meningitis in high-risk groups such as Umrah pilgrims. As many as 26.69% of Umrah pilgrims in Bengkulu were late in conducting the meningitis vaccination.Methods: Used is analytic observational research with cross sectional approach. The research sample of 122 people with purposive sampling. Data processing was performed by chi square test by looking at the value of continuity correction and pearson chi-square with α=0.05.Result: There is a significant relationship between the level of knowledge about the time of meningitis vaccination, (p=0,000) and the perseption of role of umrah travel agency (p=0,023) with the timeliness of vaccination. There was no relationship between age (p= 0,328), sex (p=0,998), level of education (p=0,868), type of work (p=1,000), level of knowledge about meningitis (p=0,477), level of knowledge about vaccination meningitis (p=0,903), family support (p=0,083) and distance access to health services (p=0,996) with timely meningitis vaccination in Umrah pilgrims.Conclusion : Knowledge about the timing of vaccination and the perseption of role of umrah travel agency are the main determining factors of the accuracy of meningitis vaccination in Umrah pilgrims.